Bioactivity and health effects of ruminant meat lipids. Invited Review. (July 2020) - Vahmani, Payam; Ponnampalam, Eric N.; Kraft, Jana; Mapiye, Cletos; Bermingham, Emma N.; Watkins, Peter J.; Proctor, Spencer D.; Dugan, Michael E.R.
Abstract: Ruminant meat (RM) is an excellent source of high-quality protein, B vitamins and trace minerals and plays an important role in global food and nutrition security. However, nutritional guidelines commonly recommend reduced intake of RM mainly because of its high saturated fatty acid (SFA) content, and more recently because of its perceived negative environmental impacts. RM is, however, rich in heart healthy cis-monounsaturated fatty acids and can be an important source of long-chain omega-3 ( n -3) fatty acids in populations with low fish consumption. In addition, RM is a source of bioactive phospholipids, as well as rumen-derived bioactive fatty acids including branched-chain, vaccenic and rumenic acids, which have been associated with several health benefits. However, the role of bioactive RM lipids in maintaining and improving consumers' health have been generally ignored in nutritional guidelines. The present review examines RM lipids in relation to human health, and evaluates the effectiveness of different feeding strategies and possibilities for future profile and content improvement.